ABMMCCS: application based multi-level mobile cache consistency scheme - Yagoub, Doha Elsharief Mahmoud; Ibrahim, Hamidah; Mamat, Ali; Othman, Mohamed (Universiti Utara Malaysia Press, 2011)
Maintaining cache consistency in mobile computing system is a critical issue due to the inheritance limitations in mobile environment such as limited network bandwidth and mobile device energy power. Most of the existing schemes maintaining mobile cache consistency support only one level of consistency that is either strict or weak which is not suitable all the time, as various mobile applications systems have different consistency requirements on their data. Also majority of the schemes restrict the using of cached data for reading only which is limits the functionality of the caching system. In this paper, a new scheme is proposed to maintain the mobile cache consistency in a single cell wireless network called Application Based Multi-Level Mobile Cache Consistency Scheme (ABMMCCS). The main idea in ABMMCCS is to be suitable to various real mobile application systems, by supporting multiple levels of consistency based on the application requirements, while saving the mobile client energy power and reducing the consumption of the network bandwidth. The initial evaluation results show that, ABMMCCM reduces the number of uplink messages issued from the mobile client, which is assist in saving the mobile client energy and better utilizing the limited network bandwidth.